A novel investigation of microbiome from vermicomposting liquid produced by Thai earthworm, Perionyx sp. 1 - Kraisittipanit, R.; Tancho, A.; Aumtong, S.; Charerntantanakul, W. (International Journal of Agricultural Technology, 2021)
The whole microbiota structure in vermicomposting liquid derived from Thai earthworm, Perionyx sp. 1 was estimated. It showed high richness microbial species and belongs to 127 species, separated in 3 fungal phyla (Ascomycota, Basidiomycota, Mucoromycota), 1 Actinomycetes and 16 bacterial phyla (Acidobacteria, Armatimonadetes, Bacteroidetes, Balneolaeota, Candidatus, Chloroflexi, Deinococcus, Fibrobacteres, Firmicutes, Gemmatimonadates, Ignavibacteriae, Nitrospirae, Planctomycetes, Proteobacteria, Tenericutes and Verrucomicrobia). The OTUs data analysis revealed the highest taxonomic abundant ratio in bacteria and fungi belong to Proteobacteria (70.20 %) and Ascomycota (5.96 %). The result confirmed that Perionyx sp. 1 VCL was high microbiota product which suitable for using for organic agriculture. Consequently, it is firstly reported in analysing the Thai-VCL microbiota by NGS technology. We successfully build up the microbial genetic database for Thai VCL for further application improvement